Effects of Governance Mediation on The Relationship Between Enterprise Risk Management and Financial Performance - Nurhayati Nurhayati (JAFFA, 2019)
This study explains the effects of mediating the role of university governance elements on the relationship between implementation of ERM and financial performance. The background of this research is inconsistency in prior studies and the phenomenon of low accountability at universities and the existence of low internal control function.  Based on the final report of Supervision, Control and Development (WASDALBIN) for the period of 2016 indicates that private universities not accredited yet are 52%. The data collection techniques applied survey methods and the data analysis techniques used Structural Equation Modeling (SEM) PLS. The results show that ERM significantly affect financial performance through the role of university governance elements.